Good Corporate Governance and Internal Audit on Financial Performance with Firm Size as a Moderating Variable in Financial Sector Companies on the Indonesia Stock Exchange, 2020-2023 - Triana, Dinda; Muhsin, Muhsin; Heniwati, Elok; Mustika, Ira Grania; Umyana, Ayu (STMIK Widya Cipta Dharma, 2024)
This study aims to analyze the impact of Good Corporate Governance (GCG) and Internal Audit on financial performance, with Firm Size as a moderating variable, in financial sector companies listed on the Indonesia Stock Exchange during the 2020–2023 period. The research employs a quantitative approach using secondary data, analyzed with Smart PLS 3. The results show that Good Corporate Governance (GCG) has a significant effect on financial performance, and Internal Audit also significantly impacts financial performance. However, Firm Size does not directly influence financial performance. Furthermore, the findings indicate that Firm Size does not moderate the relationship between Good Corporate Governance (GCG) and financial performance, nor between Internal Audit and financial performance. This study concludes that Good Corporate Governance (GCG) and Internal Audit independently affect financial performance, but Firm Size does not play a moderating role in these relationships.